Exciton-wave packet dynamics in molecular aggregates studied with pump-probe spectroscopy - Dahlbom, Mats; Minami, Tatsuya; Chernyak, Vladimir; Pullerits, Tõnu; Sundström, Villy; Mukamel, Shaul (Journal of Physical Chemistry B, 2000)
The doorway-window representation of sequential pump-probe spectroscopy, derived by solving the nonlinear exciton equations, is used to study exciton dynamics in molecular aggregates. Exciton relaxation is incorporated through a multilevel Redfield relaxation superoperator calculated using the Brownian oscillator spectral density for the collective phonon coordinates. Optical pulses are included using a mixed time and frequency domain (Wigner spectrogram) representation. Numerical results are presented for a five-chromophore model aggregate.